Public Relations Management In Enhancing The Image Of Madrasahs - Muhammad Yahya; Imam Fuadi; Asrop Safi’i (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study aims to analyze public relations management in enhancing the image of madrasahs through strategic communication, institutional relationships, managerial support, and image-building approaches. The study employed a qualitative approach with a multisite design conducted at two leading madrasahs, namely MAN Surabaya and MAN 1 Gresik. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña, combined with cross-site analysis. The findings indicate that strategic communication serves as the primary foundation for strengthening the madrasah image through digital transparency, publication of achievements, and effective social interaction. Individual relationships are reinforced through alumni networks, stakeholder collaboration, and the utilization of digital media that increases participation and public trust. Managerial support is demonstrated through digital security systems, human resource management, and technological integration based on hybrid storage and multi-layer security systems. Image development is implemented through branding strategies, publication of achievements, public relations activities, and the strengthening of visual identity and service digitalization. This study produces a conceptual framework entitled the Community–Vocational Digitalization Model, which integrates community strength, vocational orientation, and digital transformation within public relations management. The model contributes to strengthening institutional reputation, increasing public trust, and improving the competitiveness of madrasahs in responding to the challenges of modern education.